The role of the autonomic nervous system in polycystic ovary syndrome - Yu, Yue; Chen, Tong; Zheng, Zheng; Jia, Fan; Liao, Yan; Ren, Yuehan; Liu, Xinmin; Liu, Ying (Frontiers in Endocrinology, 2024)
This article reviewed the relationship between the autonomic nervous system and the development of polycystic ovary syndrome (PCOS). PCOS is the most common reproductive endocrine disorder among women of reproductive age. Its primary characteristics include persistent anovulation, hyperandrogenism, and polycystic ovarian morphology, often accompanied by disturbances in glucose and lipid metabolism. The body's functions are regulated by the autonomic nervous system, which consists mainly of the sympathetic and parasympathetic nervous systems. The autonomic nervous system helps maintain homeostasis in the body. Research indicates that ovarian function in mammals is under autonomic neural control. The ovaries receive central nervous system information through the ovarian plexus nerves and the superior ovarian nerves. Neurotransmitters mediate neural function, with acetylcholine and norepinephrine being the predominant autonomic neurotransmitters.They influence the secretion of ovarian steroids and follicular development. In animal experiments, estrogen, androgens, and stress-induced rat models have been used to explore the relationship between PCOS and the autonomic nervous system. Results have shown that the activation of the autonomic nervous system contributes to the development of PCOS in rat. In clinical practice, assessments of autonomic nervous system function in PCOS patients have been gradually employed.These assessments include heart rate variability testing, measurement of muscle sympathetic nerve activity, skin sympathetic response testing, and post-exercise heart rate recovery evaluation. PCOS patients exhibit autonomic nervous system dysfunction, characterized by increased sympathetic nervous system activity and decreased vagal nerve activity. Abnormal metabolic indicators in PCOS women can also impact autonomic nervous system activity. Clinical studies have shown that various effective methods for managing PCOS regulate patients' autonomic nervous system activity during